A 1.5 +/- 0.39 p+/-/°C Temperature-Compensated LC Oscillator Using Constant-Biased Varactors - Wang, Yong (2016)
This letter presents a temperature compensated oscillator for clock generation across a wide temperature range. The proposed technique deploys the characteristics of the constant-biased varactors to nullify the overall oscillator's temperature coefficient (TC), thereby reducing the temperature drift effect on the oscillator frequency output. Fabricated on a CMOS technology, the proposed 2.09 GHz-gm-LC oscillator sees a mere frequency drift from -20°C to 120°C. The oscillator consumes 10.9 mW at 1.4 V supply, with phase noise of -119.4 dBc/Hz at a 1 MHz offset. The demonstrated technique is useful for providing accurate clock for a variety of applications, including those operating in harsh environment.